The effect of SARS-CoV-2 infection on structural and functioal properties of arteries - I.V. Avdeeva; K.N. Polezhaeva; N.V. Burko; A.A. Khromova; Yu.A. Tomashevskaya; V.E. Oleynikov (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2022)
Background. The causative agent of SARS-CoV-2 coronavirus infection, in addition to the known effect on the respiratory system, has a pronounced destructive effect on the vascular bed. The purpose of this study is to evaluate the structural and functional properties of the large arteries in patients who had undergone COVID-19. Materials and methods. 62 people were examined, who were divided into 2 groups: the first group included 32 healthy volunteers, the second group consisted of 30 people who had suffered COVID-19. The arterial stiffness was evaluated using the method of applanation tonometry and volume sphygmography. The local stiffness of the common carotid arteries (CCA) was studied using the ultrasound with high-frequency RF signal technology. The state of the endothelium was studied by the method of flow-mediated dilation (FMD). Results. The data obtained in this study reflect the relationship between the presence of SARS-CoV-2 infection and the negative change in most parameters reflecting the structural and functional state of the arteries. Conclusions. By initiating vascular aging earlier, COVID-19 infection has adverse consequences for the structure and function of the arteries, and, as a consequence, for the cardiovascular prognosis in those who have been ill.